PELAKSANAAN BAURAN PROMOSI OBJEK WISATA QUEEN STAR WATERPARK KABUPATEN SIAK - Wardana, Tutut Dwi; ", Musadad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
The purpose of this research is to know the implementation of promotion mix conducted by Queen Star Waterpark management and to know the factors that influence the implementation of promotion mix in Queen Star Waterpark. This research uses descriptive qualitative method to analyze the problem. Data collection techniques in this study using interviews, observation and documentation. While data analysis techniques in this study using data reduction, data presentation and conclusion. Based on the research results, Queen Star Waterpark uses promotion mix, namely: Advertising, Personal Selling, Sales Promotion, Public Relations and Direct Marketing. Factors that influence the implementation of promotion mix of Queen Star Waterpark is market characteristic, product characteristic, stage in product life cycle and available fund turns out less influence in promotion. This study finds the factors that influence the way of promotion done in Queen Star Waterpark is the lack of human resources, especially the marketing and promotion, so that factors can be a constraint that affects the success of a promotion that is done. Keywords: Promotion mix